Nutritional status of children and adolescents with cancer in Scotland: A prospective cohort study. (August 2019) - Revuelta Iniesta, Raquel; Paciarotti, Ilenia; Davidson, Isobel; McKenzie, Jane M.; Brougham, Mark F.H.; Wilson, David C.
Summary: Background and aims: Malnutrition (under and overnutrition) in paediatric cancer patients during and after treatment increases short and long-term side-effects; however, factors contributing to malnutrition and patterns of change in nutritional status are still unclear. The aims were to investigate the prevalence of malnutrition, patterns of change in nutritional status and factors contributing to malnutrition in Scottish paediatric cancer patients. Methods: A prospective cohort study of Scottish children aged <18 years, diagnosed with and treated for cancer between Aug 2010 and Jan 2014 was performed. Clinical and nutritional data were collected at defined periods up to 36 months. Measurements of weight and height/length and arm anthropometry (mid-upper arm circumference (MUAC) and triceps skin-fold thickness (TSF)) were collected. Body composition was estimated from arm anthropometry using Frisancho's references and bio-electrical impedance (BIA). Malnutrition was defined according to UK BMI curves; undernutrition (<2.3rd centile; −2 SD), overweight (≥85th < 95th centile; ≥+1.05 SD < 1.63 SD) and obese (≥95th centile; ≥1.63 SD). We performed descriptive statistics and multilevel analysis. p < 0.05 was considered statistically significant. Results: Eighty-two patients [median (IQR) age 3.9 (1.9–8.8) years; 56% males] were recruited. At diagnosis, the prevalence of undernutrition was 13%, overweight 7% and obesity 15%. TSF identified the highest prevalence of undernutrition (15%) and the lowest of obesity (1%). BMI [ p < 0.001; 95% CI (1.31–3.47)] and FM (BIA) [ p < 0.05; 95% CI (0.006–0.08)] significantly increased after 3 months of treatment, whilst FFM (BIA) [ p < 0.05; 95% CI (−0.78 to (−0.01))] significantly decreased during the first three months and these patterns remained until the end of the study. High-treatment risk significantly contributed to undernutrition during the first three months of treatment [ p = 0.04; 95% CI (−16.8 to (−0.4))] and solid tumours had the highest prevalence of undernutrition [BMI (17%)]. Conclusions: Arm anthropometry (or BIA) alongside appropriate nutritional treatment that targets undernutrition initially and overnutrition at later stages should be implemented in routine clinical practice of paediatric cancer patients.